Solar Panel Repair as One of the Renewable Energy Sources in Telaga Dringo Tourism: Perbaikan Panel Surya sebagai Salah Satu Sumber Energi Terbarukan di Wisata Telaga Dringo - Aziz, Al; Fatoni, Fajar Imam; Hibaturrakhim, M. Rizal; Nurrokhmah, Laelati; Ayuandari, Nabila Putri; Fitriani, Megi Nur (Prosiding University Research Colloquium, 2024)
In the implementation of this KKN activity, there is a work program regarding the repair of solar panels at one of the tourist attractions, namely Telaga Dringo. Starting because there is no nearby electricity source from PLN that can facilitate electricity needs at the Telaga Dringo tourist spot, so solar panels were built with the aim of getting lighting at tourist attractions because considering that solar panels are tools that can convert sunlight energy into electrical energy. The problem that is currently happening in Telaga Dringo tourism is that solar panels are not running according to their function, namely converting the intensity of sunlight into electrical energy for lighting at the tourist spot. Based on the problems faced, this activity aims to extend the life of solar panels by repairing damaged solar panels, solar panels can be repaired and maximized again, increasing the efficiency of solar panel performance so that they can produce more energy, and as a renewable source of electricity at Telaga Dringo Tourism Site. The method used in this research is by conducting direct monitoring to the Telaga Dringo tourist spot by conducting initial monitoring of the location, consulting the condition of solar panels, maintaining solar panels, installing Solar Charge Controller (SCC) tools, and changing the installation network at Telaga Dringo Tourism. Implementation of solar panel repair as one of the energy sources. The method used in this research is by conducting direct monitoring to the Telaga Dringo tourist spot by conducting initial monitoring of the location, consulting the condition of solar panels, maintaining solar panels, installing Solar Charge Controller (SCC) tools, and changing the installation network at Telaga Dringo Tourism. The implementation of solar panel repair as one of the renewable energy sources at Telaga Dringo Tourism has gone well. This can be shown by the results that solar panels can produce electricity that is used to power the lights. produce electricity that is used to turn on the lights as a source of lighting at Telaga Dringo.